Expansion ⏞gis-closed & its lower separation axioms - Khattabomar, Omar Yusuf (Universitas Islam Negeri Raden Intan Lampung, 2023)
In this paper, we introduced a new classification of generalized closed sets that are called ultra-generalized s-closed sets named simply - closed sets, and we show the relationship between this new type with other open, and generalized closed sets. We also investigate advanced - continuous mappings and some of its properties. Furthermore, we discussed some lower -seperation axioms.